Comparative Pharmacokinetic Study Among 3 Metformin Formulations in Healthy Mexican Volunteers: A Single-Dose, Randomized, Open-Label, 3-Period Crossover Study - Montoya Eguía, Sandra Lucía; Garza Ocañas, Lourdes; Badillo Castañeda, Christian Tadeo; Tamez de la O, Eduardo Javier; Zanatta Calderón, María Teresa; Gómez Meza, Marco Vinicio; Garza Ulloa, Humberto Jesús (2015)
Type 2 diabetes mellitus is the most common form of diabetes. Metformin is a first-line drug for its treatment. In Mexico, there are 34 generic formulations of metformin, so brand-generic substitutions and generic-generic substitutions are a common practice. Generic products are compared only with their brand-name equivalents and not with the same product made by other manufacturers. Objective: Our aim was to establish whether 2 generic formulations of 500 mg metformin available on the Mexican market fulfill the criteria for interchangeability. Methods: This single-dose, randomized-sequence, open-label, 3-period crossover study was conducted in 12 healthy subjects in compliance with the Declaration of Helsinki and International Conference on Harmonization guidelines. A validated HPLC procedure coupled with a spectrum mass detector were used to analyze the metformin concentration in plasma samples. All pharmacokinetic analyses were performed using WinNonlin Professional Software version 6.3 (Pharsight Corporation, Sunnyvale, California). Results: Twelve healthy Mexican volunteers were enrolled in the study. Their mean age was 24.33 years and mean weight was 62.54 kg. The mean body mass index was 23.02. The values obtained for the test and reference formulations were: Cmax 1163.5 (295.2) ng/mL for treatment A, 1184.6 (215.0) ng/mL for treatment B, and 1167.8 (176.8) ng/mL for treatment C. AUC0–t was 6240.7 (1629.4) ng/mL/h for treatment A, 6433.7 (1249.8) ng/mL/h for treatment B, and 6567.1 (1145.5) ng/mL/h for treatment C. AUC0–1 was 6837.3 (1618.5) ng/mL/h for treatment A, 6911.8 (1178.4) ng/mL/h for treatment B, and 7178.6 (1086.8) ng/mL/h for treatment C. Conclusions: The test formulation 500-mg metformin tablets were bioequivalent to the reference formulation and to each other, according to the general laws of health care in Mexico.